Phenotypic variability in human skin mast cells. Issue 6 (13th February 2016) - Babina, Magda; Guhl, Sven; Artuc, Metin; Trivedi, Neil N.; Zuberbier, Torsten
Abstract: Mast cells (MCs) are unique constituents of the human body. While inter‐individual differences may influence the ways by which MCs operate in their skin habitat, they have not been surveyed in a comprehensive manner so far. We therefore set out to quantify skin MC variability in a large cohort of subjects. Pathophysiologically relevant key features were quantified and correlated: transcripts of c‐kit, Fc ε RI α, Fc ε RI β, Fc ε RI γ, histidine decarboxylase, tryptase, and chymase; surface expression of c‐Kit, Fc ε RI α ; activity of tryptase, and chymase; histamine content and release triggered by Fc ε RI and Ca 2+ ionophore. While there was substantial variability among subjects, it strongly depended on the feature under study (coefficient of variation 33‐386%). Surface expression of Fc ε RI was positively associated with Fc ε RI α mRNA content, histamine content with HDC mRNA, and chymase activity with chymase mRNA. Also, MC signature genes were co‐regulated in distinct patterns. Intriguingly, histamine levels were positively linked to tryptase and chymase activity, whereas tryptase and chymase activity appeared to be uncorrelated. Fc ε RI triggered histamine release was highly variable and was unrelated to Fc ε RI expression but unexpectedly tightly correlated with histamine release elicited by Ca 2+ ionophore. This most comprehensive and systematic work of its kind provides not only detailed insights into inter‐individual variability in MCs, but also uncovers unexpected patterns of co‐regulation among signature attributes of the lineage. Differences in MCs among humans may well underlie clinical responses in settings of allergic reactions and complex skin disorders alike.